FACTORS RELATING TO TURNOVER INTENTION OF MEDICAL SALES REPRESENTATIVES OF BDSH THAILAND LTD. - Praditbatuga, Piyathida; Phakcharoen, Oranich (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
This research aims to study whether job satisfaction in terms of Pay, Promotion, Supervision, Fringe Benefits, Contingent Rewards, Operating Conditions, Coworkers, Nature of Work, and Communication has a relationship with the turnover intention of medical sales representatives in BDSH Thailand Ltd. The questionnaire was used as a research instrument to collect data. The data was collected from all 230 medical sales representatives in BDSH Thailand Ltd. Pearson’s correlation analysis was used to test the research hypotheses. The results of this research revealed that turnover intention had a very low positive relationship with pay, promotion, and contingent rewards of medical sales representatives in BDSH Thailand Ltd. In addition, supervision, fringe benefit, operating procedures, coworkers, nature of work, and communication did not have a relationship with the turnover intention of medical sales representatives. This finding contrasts with many previous research studies which found a strong negative relationship between job satisfaction and turnover intention. This may be because of the characteristic of medical sales representatives in BDSH Thailand may different from other jobs. Medical sales representative in BDSH Thailand faces pressure from their job requirement for volume of minimum sales per month. Therefore, Pay, Promotion, and Contingent reward may not be the factors that influence their intention to leave the company.